Exponential approximation of multivariate bandlimited functions from average oversampling. Issue 1 (2nd January 2022) - Chen, Wenjian; Zhang, Haizhang
ABSTRACT: Instead of sampling a function at a single point, average sampling takes the weighted sum of function values around the point. Such a sampling strategy is more practical and more stable. In this note, we present an explicit method with an exponentially-decaying approximation error to reconstruct a multivariate bandlimited function from its finite average oversampling data. The key problem in our analysis is how to extend a function so that its inverse Fourier transform decays at an optimal rate to zero at infinity.